Aging and Place in Long-Term Care Settings: Influences on Social Relationships. (December 2014) - Bonifas, Robin P.; Simons, Kelsey; Biel, Barbara; Kramer, Christie
Objective: This article presents results of a qualitative research study that examined how living in a long-term care (LTC) home influences the quality of residents' relationships with peers, family members, and outside friends.Method: Semistructured interviews using a phenomenological approach were conducted with 23 residents of a LTC home. Thematic analysis was employed to illuminate residents' perspectives on the nature of social relationships in this setting.Results: Four key themes were identified that highlight the role of place in social relationships. Residing in a LTC home influences the context of social interactions, impacts their quality and process, clusters individuals with health and functional declines that hinder socialization, and poses structural and cultural barriers that impede social interactions. Health and functional limitations posed the greatest challenge to socialization relative to characteristics of the facility itself.Discussion: Residents' insights emphasize how personal characteristics influence community culture and the experience of place.